Adverse psychosocial factors in pregnancy and preterm delivery. Issue 5 (5th March 2021) - Haviland, Miriam J.; Nillni, Yael I.; Cabral, Howard J.; Fox, Matthew P.; Wise, Lauren A.; Burris, Heather H.; Hacker, Michele R.
Abstract: Background: Mental health symptoms, stress, and low psychosocial resources are associated with preterm delivery. It is unknown if there are groups of women who experience similar patterns of these adverse psychosocial factors during pregnancy and if the risk of preterm delivery differs among these groups. Objective: To identify groups of women with similar patterns of adverse psychosocial factors during pregnancy and determine whether the risk of preterm delivery differs among these groups. Methods: Spontaneous Prematurity and Epigenetics of the Cervix (SPEC) is a prospective cohort study of pregnant women, aged 18 and older. In this analysis, we included women who enrolled after 24 August 2014 and delivered by 20 January 2019. As women could enrol more than once, our cohort included 774 women with 787 pregnancies. We conducted a latent class analysis to identify groups of women with similar patterns of adverse psychosocial factors during pregnancy based on their responses to measures assessing depression, perceived stress, anxiety (pregnancy‐related and generalised), stressful life events, resilience, and social support (partner and friend/family). After identifying the latent classes, we used log‐binomial regression to compare the incidence of preterm delivery among the classes. Results: The median age among participants was 33.2 years (interquartile range 30.3‐36.3), and the majority were non‐Hispanic white (56.9%). We identified three classes of adverse psychosocial factors (few, some, and many factors). In total, 63 (8.0%) pregnancies resulted in a preterm delivery. Compared to participants with few factors, the risk of preterm delivery was no different among participants with some (RR 1.23, 95% CI 0.68, 2.25) and many adverse factors (RR 1.62, 95% CI 0.73, 3.62). Conclusions: We identified three groups of pregnant women with similar patterns of adverse psychosocial factors. We did not observe a difference in the risk of preterm delivery among the classes.